2020
DOI: 10.1021/acs.jmedchem.9b01942
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-based Differential Targeting of PPI Stabilizer Interfaces

Abstract: Stabilization of protein–protein interactions (PPIs) holds great potential for therapeutic agents, as illustrated by the successful drugs rapamycin and lenalidomide. However, how such interface-binding molecules can be created in a rational, bottom-up manner is a largely unanswered question. We report here how a fragment-based approach can be used to identify chemical starting points for the development of small-molecule stabilizers that differentiate between two different PPI interfaces of the adapter protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…100 There is fragments that represent promising starting points for the development of specific 14-3-3 PPI stabilizers has also been reported resently. 101 Studies have shown that some small-molecule anticancer agents can prevent binding of 14-3-3 by inhibiting phosphorylation of the target protein. For example, UCN-01 can inhibit the activity of CHK1, TAK, CHK2 and other kinases, and thus phosphorylation of Ser216, the 14-3-3-binding site on CDC25C.…”
Section: Ther Apeuti C Targ E Ting Of 14 -3 -3 Protein Smentioning
confidence: 99%
“…100 There is fragments that represent promising starting points for the development of specific 14-3-3 PPI stabilizers has also been reported resently. 101 Studies have shown that some small-molecule anticancer agents can prevent binding of 14-3-3 by inhibiting phosphorylation of the target protein. For example, UCN-01 can inhibit the activity of CHK1, TAK, CHK2 and other kinases, and thus phosphorylation of Ser216, the 14-3-3-binding site on CDC25C.…”
Section: Ther Apeuti C Targ E Ting Of 14 -3 -3 Protein Smentioning
confidence: 99%
“…AZ-008: AZ-008 was discovered as a weak stabiliser of this PPI during a fragment-based drug discovery campaign 24 . FP and SPR experiments indicated that the compound has a reproducible two-fold stabilisation effect.…”
Section: Role In P53 Regulationmentioning
confidence: 99%
“…In recent studies, the reverse experiment, monitoring 15 N, 2 H-labeled 14-3-3ΔC protein in 1 H, 15 N-TROSY-HSQC experiments [ 103 ], was used to investigate the stabilizing effect of several compounds on the interaction of 14-3-3 with different unlabeled peptide epitopes derived from 14-3-3 cargo proteins [ 104 106 ]. E.g., a semi-synthetic ligand consisting of a fusicoccane diterpene core combined with different sugar moieties was designed to improve its properties as molecular glue for the 14-3-3/p53 complex [ 105 ].…”
Section: Reviewmentioning
confidence: 99%